Pengaruh Good Corporate Governance Terhadap Kinerja Keuangan Pada Perusahaan Telekomunikasi yang Terdaftar di BEI Pada Tahun 2020-2024 - Ni Kadek Dwi Pradnya Dewi; Ni Luh Gede Erni Sulindawati; Putu Riesty Masdiantini (Universitas Pendidikan Ganesha, 2025)
This study aimed to examine the effect of independent board of commissioners, managerial ownership, institutional ownership, and audit committee on the financial performance of telecommunication companies listed on the Indonesia Stock Exchange (IDX) during the period 2020–2024. The research problem was motivated by the lack of good corporate governance implementation in telecommunication companies and the decline in financial performance. The population consisted of all telecommunication companies listed on the IDX from 2020 to 2024. Data collection was conducted using the documentation method, and the sample was selected through purposive sampling. The final sample included 17 companies, with a total of 85 observations. The data were analyzed using multiple linear regression analysis. The results of the study indicated that, partially, the independent board of commissioners, managerial ownership, institutional ownership, and audit committee had a significant positive effect on financial performance. These findings implied that strengthening corporate governance through the roles of independent commissioners, managerial ownership, institutional ownership, and an effective audit committee could promote the sustainable improvement of a company's financial performance.